2011
DOI: 10.1128/iai.00022-11
|View full text |Cite
|
Sign up to set email alerts
|

The Toll-Like Receptor 4 Agonist Monophosphoryl Lipid A Augments Innate Host Resistance to Systemic Bacterial Infection

Abstract: Monophosphoryl lipid A (MPLA) is a Toll-like receptor 4 (TLR4) agonist that is currently used as a vaccine adjuvant in humans. In this study, we evaluated the effect of MPLA treatment on the innate immune response to systemic bacterial infections in mice. Mice treated with MPLA after burn injury showed improved survival and less local and systemic dissemination of bacteria in a model of Pseudomonas aeruginosa burn wound infection. Prophylactic treatment with MPLA significantly enhanced bacterial clearance at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 40 publications
(37 reference statements)
8
114
0
2
Order By: Relevance
“…It was shown that TLR4 stimulation leads to enhanced phagocytosis of bacteria by macrophages (15). Furthermore, other investigators showed that agonists of TLR4 (33,46) or other TLRs (46), given either as a pretreatment or early postinfection, enhance bacterial clearance and survival in models of sepsis. We confirm in our current work that LPS given 1 h after CLP improves bacterial clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that TLR4 stimulation leads to enhanced phagocytosis of bacteria by macrophages (15). Furthermore, other investigators showed that agonists of TLR4 (33,46) or other TLRs (46), given either as a pretreatment or early postinfection, enhance bacterial clearance and survival in models of sepsis. We confirm in our current work that LPS given 1 h after CLP improves bacterial clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, tissue damage, and lethality are diminished in the absence of TLR4 signaling (29). However, in the setting of infection with live bacteria, the contribution of TLR4 varies depending on the experimental model and type of organism used in the study (13)(14)(15)(30)(31)(32)(33)(34)(35)(36)(37). Most early studies used mouse strains with mutant forms of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…MPLA is a detoxified form of the endotoxin lipopolysaccharide recognised by TLR-4 (Johnson et al, 1987) and is used as a vaccine adjuvant in humans (Thoelen et al, 1998). The MPLA improves the innate immune response to bacterial infections by increasing the number of cells with phagocytic functions at the sites of infection, which in turn enhances the bacterial clearance (Romero et al, 2011). This adjuvant is also able to stimulate the adaptive immune response by promoting the differentiation of CD4+ T cells into IFNγ-producing Th1 cells in mice (Thompson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 mediates LPS responsiveness and recognizes Gram-negative bacteria via the LPS moiety on the surface of these microorganisms. Some researchers have reported that MPL treatment promotes neutrophil recruitment to the infectious source and mediates protection against both lethal systemic bacterial infection and nasopharyngeal colonization (28,29); however, little is known about whether the induction of innate immunity via TLR4 contributes to the protective immune response against bacterial infection. Therefore, in the current study, we used UT12, a new TLR4 agonistic monoclonal antibody, to address whether the promotion of innate host resistance through TLR4 mediates protection against secondary pneumococcal pneumonia following influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%